"Bucking" for a Diagnosis. Issue 5 (May 2015) - Leva, Ernest G.; Stern, Steven P.; Miele, Niel F.
<x xml:space="preserve">Abstract</x> Abstract Foreign body ingestions are all too common in children. The adverse effects of many of these ingestions are well known. We present an interesting case report of "Buckyballs" and the implications of ingesting or placing in other orifices these strong rare-earth magnets. We illustrate that these toys can be of possible disastrous consequences. Although these products were removed from the marketplace, there is still the possibility of negative consequences. Our aim was to inform the physician population of their persistence and negative effects.